The Dynamics of Halal Food Industry: A Comparative Analysis of Multiculturalism and Bureaucracy in South Korea and Indonesia (2014-2019) - Paraswati, Ramita; Rosyid , Muhammad; Soimatul SaΓÇÖadah, Sonia (Harmoni, 2024)
AbstractThis study identified a clear paradox in the halal food sector between Muslim and non-Muslim countries. It explored the surprising fact that despite being the country with the highest number of Muslims in the world, Indonesia lags behind in exporting halal food, while South Korea, a non-Muslim country, leads the market. This study offered a novel comparative analysis of the socio-cultural and economic dynamics shaping the halal food industry in Indonesia and South Korea, employing a multidisciplinary theoretical framework to enrich the discourse on global halal market development. Ibn KhaldunΓÇÖs theory on the role of immigrants in innovation, Max WeberΓÇÖs thesis on the spirit of capitalism, and Faisal KarimΓÇÖs role theory are integrated to investigate how these frameworks illuminate the contrasting policy approaches and economic outcomes in the two countries. Using a comparative research method focusing on the period 2014ΓÇô2019, this study highlighted the intersection of multiculturalism in Indonesia and monoculturalism in South Korea, examining their respective impacts on policymaking and bureaucratic strategies in fostering the halal food market. The findings revealed that South Korea's inclusive immigration policies, driven by demographic challenges, have fostered greater efficiency and innovation within its halal market, enabling it to dominate despite its small Muslim population. Conversely, Indonesia, even its significant Muslim majority, faces bureaucratic inefficiency policy on halal certification, which hinder its potential to lead in the halal sector. The study concluded that South KoreaΓÇÖs strategic use of inclusive immigrant policy and proactive economic rationality have been pivotal to its success, while IndonesiaΓÇÖs fragmented policy framework has constrained its progress. This research contributed to the broader understanding of how religion, socio-cultural dynamics, and policymaking intersect with economic systems, offering practical insights for nations aiming to optimize their middle-power capabilities in the global halal food industry.